(3bQGAGJ aj GdacQ GdGOGQj GdeYGUQ (B:s (3JHGjf GdGgOGa GdeJhNGI ef JHfj GdeSDhdjI GdGLJeGYjI aj GdefXeGJ GdMchejI h GdNGUI (B/s - (3GdNaGLj, fYeI YHGSs; (3GdZGdHj, WGgQ eMSf s ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2008)
(3GdMGcejI h GdefXhQ GdCNdGbj dgG aj GdeDSSGJ, GdLhOI , GdYbd GdGOGQj , GdQjGOI h QCS GdeGd GdeYQaI , GdNWQ , GdCNdGb h GdeSDhdjI GdGLJeGYjI (B.s
(3eQGLY U(B.355s
Keywords: (3GdEOGQI GdYGeIs; (3GdeSDhdjI GdGLJeGYjIs; (3GdefXeI GdMchejIs